VALUE ADDED TAX DIMENSION: THE CASE OF LITHUANIA - Bikas, Egidijus; Raškauskas, Julius (Ekonomika, 2011)
The article sums up works of different scientists, dealing with the impact of value added tax (VAT) on the economy of some countries. The authors analyse the Lithuanian VAT structure, the dynamics of income from this tax and amendments in the Law on Value Added Tax in terms of narrowing and widening the taxable base according to the theoretical analysis of the sources. It is aimed to determine the impact of VAT standard tariff, reduced tariffs and shadow economy on income from this tax. Multiple regression, correlation, optimization and C-effectiveness ratio are used for the analysis. The analysis has revealed that amendments in the Law on Value Added Tax in terms of narrowing and widening the taxable base influenced the amount of income from VAT collected to the budget.